HASRAT, TRAUMA, DAN ABSURDITAS TOKOH DALAM NOVEL SEPORSI MIE AYAM SEBELUM MATI KARYA BRIAN KHRISNA - Mukti, Sry Aji Prabowo; Rengganis, Ririe (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2025)
This article aims to reveal the dynamics of desire, trauma, and absurdity in the character Ale through an interdisciplinary approach between Jacques Lacan's psychoanalysis and Jean-Paul Sartre's existentialism. The scope of the study includes narrative and psychological analysis of the main character in the novel Seporsi Mie Ayam Sebelum Mati by Brian Khrisna. The method used is content analysis with close reading techniques on relevant text units. Data were obtained from narrative excerpts, monologues, and dialogues that reflect the psychic structure and existential reflection of the character. The results of the study show that the act of eating chicken noodles is not merely a form of escape, but a symbol of desire born from past trauma (Lacan) and authentic choices in facing the absurdity of life (Sartre). An interesting fact in this finding is that the symbols used by the author in the novel add depth to the meaning as a representation of loss, longing, and the formation of existential meaning. This study confirms that popular fiction can be a medium for reflection on the complexity of the human mind, while also showing the importance of an interdisciplinary approach in contemporary Indonesian literary studies.